A Return to Servitude : Maya Migration and the Tourist Trade in Cancún - Castellanos, María Bianet (Book collections on Project MUSE., 2010)
As a free trade zone and Latin America's most popular destination, Cancún, Mexico, is more than just a tourist town. It is not only actively involved in the production of transnational capital but also forms an integral part of the state's modernization plan for rural, indigenous communities. Indeed, Maya migrants make up over a third of the city's population. A Return to Servitude is an ethnography of Maya migration within Mexico that analyzes the foundational role indigenous peoples play in the development of the modern nation-state. Focusing on tourism in the Yucatán Peninsula, M. Bianet Ca.